The need for developing knowledge of registered nurses on transcultural nursing - Malliarou, Maria; Karathanasi, Konstantinia; Sarafis, Pavlos (My University, 2009)
Individuals and families belong to several cultural groups. Each individual has the right to be respected for his or her unique differences and cultural heritage. Caregivers who can assess, plan, and intervene in a culturally competent manner will improve the care of clients for whom they care. Learning culture is an ongoing process and develops in a variety of ways, but primarily through cultural encounters.
Keywords: Transcultural nursing